Electrochemical and biosensing applications of biochar and biochar-based composites - Tshoko, Siphokazi; Mulaudzi-Masuku, Takalani; Iwuoha, Emmanuel; Ngece-Ajayi, Rachel Fanelwa (Frontiers in Sensors, 2025)
Biochar, a carbon-rich substance produced through biomass pyrolysis, has attracted considerable interest due to its wide-ranging applications, including in electrochemical sensing and biosensing. Their distinctive physicochemical characteristics, such as a large surface area, adjustable porosity, plentiful functional groups and outstanding electrical conductivity, render it a promising choice for electrode materials and sensor systems. The integration of biochar into composite materials alongside metals, metal oxides, polymers and nanomaterials has further augmented its electrochemical capabilities, leading to enhancements in sensitivity, selectivity and stability in sensing applications. This review offers an extensive summary of recent developments in biochar-based electrochemical sensors and biosensors, concentrating on their design, functionalization techniques and use in detecting biomolecules, environmental contaminants and electroactive species. We explore the fundamental mechanisms that drive biochar’s electrochemical behavior and underscore the collaborative effects between biochar and various composite materials in boosting sensor efficiency. Furthermore, we delve into the challenges and future prospects of biochar-based sensing technologies, highlighting their potential for creating sustainable and cost-effective analytical tools.